Comparative Efficacy of Systemic VS Intratympanic Corticosteroid Therapy in the Management of Sudden Sensorineural Hearing Loss - Abdul Manan Khan, Aria Masoom (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Sudden sensorineural hearing loss is a major health problem that negatively affects the life of an individual. So specific therapy is essential. Objective: The aim of this study as to compare the effectiveness of systemic versus Intratympanic Corticosteroid therapy in the management of SSNHL. Material and method: The current study was conducted at the Department of ENT, Bolan Medical College / Complex Hospital, Quetta from January 2022 to June 2022 after taking approval from the research committee of the institute. A total of 128 individuals of both genders and different age groups (18-65 years) with SSNHL were included. Participants in the study were divided into two groups based on the method of corticosteroid administration: Systemic Therapy Group who received oral prednisolone and Intratympanic therapy group who got weekly intratympanic injections of dexamethasone. Pure-tone audiometry (PTA) was used to conduct audiological evaluations. Version 25 of the SPSS was used to analyze the data. For categorical data, the chi-square test was used, and for continuous variables, either an independent t-test or a paired t-test was employed. The p-value was less than 0.05 was considered statistically significant. Results: A total of 128 individuals were included in this study. Significant differences were seen when the recovery results of the two therapy groups were compared. Of the 74 people who participated in the systemic treatment group, 30 (40.5%) showed full recovery, 26 (35.1%) showed partial recovery, and 18 (24.3%) showed no recovery. On the other hand, of the 54 individuals, 12 (22.2%) showed full recovery, 18 (33.3%) showed partial recovery, and 24 (44.4%) showed no recovery in the intratympanic treatment group. The reduction in pure tune audiometry (PTA) was also assessed as an indicator of treatment effectiveness. The mean PTA improvement was 25.5 ± 10 dB in the systemic therapy group and 19.2 ± 9 dB in the intratympanic therapy group; the difference was statistically significant (p=0.02). Conclusion: The current study concluded that in the management of SSNHL systemic corticosteroid therapy is more effective and revealed a significant improvement in hearing recovery, PTA transition, and the speed of symptom resolution as compared to intratympanic therapy. Keywords: Efficacy; Systemic; Intratympanic; Corticosteroid; Sensorineural Hearing Loss